Christian Ethics as an Effort to Address Moral Crisis in Juvenile Delinquency - Kadili, Trivena Enjel; Boiliu, Esti Regina; Triposa, Reni (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the role of Christian ethics as a strategic framework to address moral crises associated with juvenile delinquency. Juvenile delinquency is a complex social phenomenon influenced by intrinsic and extrinsic factors, including family dynamics, peer relationships, educational environments, digital media exposure, and spiritual formation. The study employs a qualitative descriptive approach, integrating data from interviews, observations, and document analysis, validated through triangulation techniques. Findings indicate that Christian ethics, grounded in biblical principles such as love, forgiveness, responsibility, and self-discipline, provides a holistic moral framework that guides adolescents toward ethical decision-making and constructive behavior. The transformative work of the Holy Spirit is highlighted as a central mechanism for internal moral renewal, fostering self-control and spiritual discernment that counteract tendencies toward delinquent behavior.